Understanding Water-Society Nexus: Insights From Turkey's Small-Scale Hydropower Policy - Kibaroğlu, Ayşegül; Sayan, Ramazan Caner (Water Policy, 2016)
Turkey’s recent venture involving the construction of hundreds of small-scale hydropower projects is a signifi- cant trend, both in regard to its contribution to Turkey’s hydroelectricity production and the social and environmental impact of these projects at the local level. Turkey’s hydropower policy was premised on a conven- tional understanding of water driven by science, technology, and the market. This approach, however, does not seem to have paid sufficient attention to the socio-ecological characteristics of water. Developing policies from a solely technical perspective creates political, economic, and cultural inequalities that adversely affect the social and ecological realm. Hence, this paper attempts to deconstruct the design, execution, and aftermath of Turkey’s small-scale hydropower policy through the lens of the hydro-social cycle. We aim to explain various dimensions of Turkey’s small-scale hydropower program in a conceptual framework that merges the concept of the hydro-social cycle with patterns of distributive environmental justice. We find that state-led, techno-centric and market-oriented approaches to water instrumentalize a rhetoric of justice in order to justify the development of small-scale hydropower ventures. Our analysis, however, demonstrates Turkey’s small-scale hydropower policy falls short of delivering on its promise of distributive justice in three relevant dimensions, namely the distribution of burdens and benefits, vulnerabilities, and responsibilities at local level.
Keywords: Small scale hydro-power; Turkey; Water policy; Hydro-Social Cycle; Distributive Environmental Justice; Water Policy; Small-Scale Hydropower